KAJIAN PREFERENSI KONSUMEN TERHADAP BEBERAPA VARIETAS UNGGUL BARU PADI SAWAH MELALUI UJI ORGANOLEPTIK BERAS DAN NASI - Umi Barokah; Daenuri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Rice is a staple food for most Indonesian people. The size of rice consumption (consumer acceptance of rice) is determined by the quality of the rice produced. The fluffier the rice produced tends to be more in demand by the public. Organoleptic tests using panelists (tasters) are often used in assessing the quality of various types of food. The approach with organoleptic assessment is considered the most practical and less costly. The purpose of this study was to determine consumer preferences for several new superior varieties of lowland rice through organoleptic tests of rice and rice. The organoleptic test was carried out at Ma'arif Nahdlatul Ulama University Kebumen on December 18, 2020. The materials tested in the organoleptic test of rice and rice were eleven varieties of rice harvested from the adaptation test of new high yielding varieties of lowland rice based on the application of integrated technology in Karangsambung District, Kebumen Regency. The eleven new rice varieties used were Inpari 30, Inpari 32, Inpari 33, Inpari 42, Inpari 43, Inpari 44, Siliwangi, Padjajaran, Cakrabuana, Ciherang and IR 64. Panelists as respondents were given samples of rice and rice, then given the opportunity to see, smell, hold, smell and taste (especially rice) and then gave an assessment. The results of the assessment are recapitulated and presented in the form of tables and graphs for further descriptive analysis. The conclusion that can be drawn after the organoleptic test is known that Inpari 33 Rice is the most preferred variety by the panelists because it is shiny, long in shape and has the best ranking. For rice, the panelists preferred the Siliwangi variety because in terms of aroma, it was slightly fragrant, fluffier, had the best ranking and the highest hedonic test score. Keywords: variety, superior, new, rice